Public private partnership? - Manoj Kumar, T.K. (2005)
In this article, the author explores the need for public private partnership, and attempts to arrive at a definition of PPP. He traces the various forms of PPPs possible and explains the Special Purpose Vehicle (SPV) mode of PPP in some depth. He concludes by giving two examples of PPPs undertaken through this route in India, which may prove good areas for further study in this subject. - Reproduced.
Keywords: Public private partnership